2006
DOI: 10.1158/1055-9965.epi-05-0437
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to Participate in Genetics Research among African American Smokers

Abstract: Although prior studies have shown that African American smokers are likely to carry some of the genetic variants associated with smoking risk, additional research with African American smokers is needed to replicate these findings. Limited information is available on interest in participating in research to identify genetic risk factors for smoking among African American smokers; therefore, the goals of the present study were to describe intentions to participate in smoking and genetics research, and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 18 publications
3
72
0
Order By: Relevance
“…All previous studies of US adults and adolescents found that the majority of respondents (57-91%) were interested in genetic testing related to smoking [15,16,18,19]. However, the statistics reported in all but one [16] of these studies were aggregated across respondents with diverse or unknown smoking histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All previous studies of US adults and adolescents found that the majority of respondents (57-91%) were interested in genetic testing related to smoking [15,16,18,19]. However, the statistics reported in all but one [16] of these studies were aggregated across respondents with diverse or unknown smoking histories.…”
Section: Discussionmentioning
confidence: 99%
“…The few existing studies of public perception have found moderate to high levels of interest in genetic testing predicting nicotine dependence among both smokers and nonsmokers within hypothetical testing scenarios [15,16,17,18,19]. Qualitative methods have begun to yield deeper insights into the complexity of individuals' motivations for testing.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic susceptibility and its implications for treatment and prevention can matter to prospective minority research participants. One study found that African Americans involved in genetic variant research on smoking susceptibility cited future use of genetic information to improve cessation programs as a reason for participation [54]. Approaches which target those predisposed to participation provide culturally tailored and accessible materials, foster trustworthiness, and employ flexible methods, and evaluation measures can be applied to maximize involvement of racial and/or ethnic minorities and other marginalized groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical oversight, language preference, clarity of communications (Kozlowski et al 2002), beliefs about benefits of participation (Halbert et al 2006), and trust between participants and investigators (Corbie-Smith et al 2002) should not be ignored. Contextual factors such as study design and recruitment efforts (Bhutta et al 2013;James et al 2008;Lanfear et al 2011;Patterson et al 2008), incentives (Bhatti et al 2009;Crider et al 2006;McCarty et al 2007), and the method of subject interaction (Etter et al 1998) can also influence participation rates.…”
Section: Introductionmentioning
confidence: 99%